Epidemiological profile of gestational syphilis and its influence on vertical transmission in the City of Parnamirim-RN (Research, Society and Development, 2021)
Objective: To analyze the epidemiological profile of cases of gestational syphilis in the city of Parnamirim - NB and the factors predisposed to the incidence of congenital syphilis, from 2010 to 2019. Methodology: Observational and descriptive study of the indicators: detection rate/1000 live births of gestational and congenital syphilis; profile in pregnant women and the care situation in prenatal care. Results: It was observed oscillation of the cases during the period, with gestational syphilis, with maximum of 11.7/1000 in 2018 and congenital, with 2.3/1,000 in 2019. There was a higher frequency in the 20 to 29 years age group, totaling 51%, incomplete elementary level (39.4%), gestational age of diagnosis in the third trimester (44.1%) and clinical classification for latent syphilis (53%). In the care model, prenatal care was frequently performed, with a maximum of 88.5%; in the period of diagnosis during delivery and postpartum (52.9%); and, regarding the treatment schedule, 76% were inadequate. Regarding the PHC indicator, there was a decrease during the period, with 61.7% for FHS coverage and 72.5% for PC in 2019. Conclusion: We observed oscillation of syphilis cases, exposing gaps in the control of the disease, and failures in the primary care model arranged in the municipality, especially during prenatal care, thus increasing the risks of vertical transmission for syphilis.